Utilization of Ultrasonication as a Method of Reducing Organic and Inorganic Contamination in Post‐Consumer Plastic Film Waste - Victor S. Cecon; Mita Munshi; Shahnaz Mukta; Keith L. Vorst; Greg W. Curtzwiler (Macromolecular Materials and Engineering)
Abstract Post‐consumer plastic film waste often carries organic and inorganic contaminants that challenge recycling processes and affect the quality of recycled products. An effective contaminant removal procedure through washing such single‐used plastic films (SUPFs) can address environmental and waste management concerns. This study compares the efficiency of different washing techniques in reducing SUPF contamination. To evaluate the efficacy of each washing technique, film samples collected from material recovery facilities are individually exposed to friction, ultrasonic‐assisted, and a combination of both washes. Thermal analysis indicates that the polymers' melting temperature, crystallization temperature, and crystallinity remain unaffected by the washing methods, demonstrating method aptness. Confocal laser scanning microscope images show that washing results in a cleaner sample surface. 91% ash reduction during the combined wash treatment indicates a high method efficiency compared to the individual friction and ultrasonic wash procedures. This is further validated by reducing characteristic contaminant IR bands (3600–3000, 1750–1600, and 1100–1000 cm−1). Elements of concern such as Cd, Cr, Hg, and Pb in SUPFs after each washing technique applied conform with regulations (<100 ppm) for packaging products. This research shows the novel ultrasonic washing reduces more contamination than friction with shorter wash times and no surfactants.